2017
DOI: 10.1038/s41598-017-04592-x
|View full text |Cite
|
Sign up to set email alerts
|

Karst tiankengs as refugia for indigenous tree flora amidst a degraded landscape in southwestern China

Abstract: We conducted floristic and community analyses to compare the floristic composition, forest structure, taxonomic richness, and species diversity between two tiankeng (large doline, or sinkhole) habitats and two outside-tiankeng habitats of forest fragments in a degraded karst area in southwestern China. We found remarkably higher taxonomic richness in the tiankeng habitats than in the outside-tiankeng habitats at the species, generic, and familial levels. The inside-tiankeng habitats had higher floristic divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 35 publications
0
60
0
Order By: Relevance
“…Rank-abundance plot, also called diversity-dominance curve, visualizes the community dominance and evenness as well as species richness of an ecosystem in a two-dimensional graph. A steeper curve indicates greater community dominance and less evenness of species patterns in an ecosystem [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Rank-abundance plot, also called diversity-dominance curve, visualizes the community dominance and evenness as well as species richness of an ecosystem in a two-dimensional graph. A steeper curve indicates greater community dominance and less evenness of species patterns in an ecosystem [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Arable lands are confined to valleys, foothills, and soil‐filled sinkholes in karst regions, and they are the first to be converted to farmlands and homesteads (Su et al . ). Historically, people did not cultivate karst hilltops and upper slopes where water and nutrients were lacking, but land shortage and development policies have caused deforestation even in upper slopes and hilltops (Yan & Cai ).…”
Section: Impacts From Natural and Anthropogenic Disturbances On Karstmentioning
confidence: 97%
“…Sinkholes have complex environmental characteristics because of their unique geomorphology (Zhu et al 2003;B atori et al 2014;Shui et al 2015;Su et al 2017;Hofierka et al 2018). Environmental researchers have found that sinkholes have the potential to act as a geophysical well for higher concentrations of contaminant deposition from traffic (Theodore et al 2008;Wang et al 2009;Kong et al 2011Kong et al , 2012Liu & Zhang 2019).…”
Section: Introductionmentioning
confidence: 99%